Manual for the design of concrete building structures to Eurocode 2 (Institution of Structural Engineers, 2006)
This manual supports the design of structures to BS EN 1992-1-1: 2004 and BS EN 1992-1-2: 2004 for construction in the UK. The Nationally Determined Parameters from the UK National Annex have been incorporated in the design formulae that are presented. The range of structures and structural elements covered by the manual is limited to building structures that do not rely on bending in columns for their resistance to horizontal forces and are also non-sway. -- Provided by publisher.
"BCA, The Concrete Centre"--Cover
Keywords: Concrete construction -- Design and construction -- Standards.; Structural analysis (Engineering); Eurocodes (Standards); elektronické knihy; electronic books